Perempuan dan Ketidakadilan: Review atas Beberapa Isu Gender Menyangkut Dunia Kerja - Rasyidah, Ida; Aini, Noeryamin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
This article endeavours to offer a review of the literature on gender issues pertaining to the world of employment. It starts with a consideration of gender mainstreaming in the world and how Indonesia adopts this gender mainstreaming program in government policies. It continues by reviewing gender issues pertaining to their relations to development. By looking at the concept and the ideology of work distribution along sexual lines we may learn of the ways injustice in the organization of the structure and the culture of work is created. Through the review of a number of works we may conclude that patriarchal ideology has stigmatized woman and the strong divide in gender roles has resulted in a gender biased system of the organization of work.DOI: 10.15408/sdi.v16i1.493